Konsep Etika Epikuros dan Problem Media Sosial - Afif, Bahrul (Universitas Islam Negeri Raden Intan Lampung, 2019)
In the last few decades, one of the ethical problems that has taken a lot of public attention is the hoax problem on social media. Social media, which was originally created as a medium to facilitate the delivery of messages and information, is actually being misused to spread false news which eventually breeds hatred and animosity. One philosopher who is famous for his thoughts on ethical concepts, namely Epicurean. This article will discuss how the Epikuros ethical concept and its relevance to social media problems. This paper is classified in library research and uses the hermeneutical descriptive method. The typology of Epicurean thought belongs to the ethical theory of hedonism, Epicurean in its ethical thought establishes pleasure or pleasure (hedone) as the highest ideal in human life. The intended enjoyment is not only from the material aspect, but the most important thing is the enjoyment of the soul which is referred to as ataraxia. To achieve ataraxia that is by trying to avoid suffering and anxiety. According to Epicureans, in order to avoid suffering and anxiety, humans must have the attitude of phronesis or prudence, which is interpreted as an attitude of vigilance. When connected with social media problems, this attitude of vigilance is very relevant and important to be owned by every individual as a user of social media, so as not to become part of the chain of hoax distribution.